Operando Raman Shift Replaces Current in Electrochemical Analysis of Li-ion Batteries: A Comparative Study - Mariusz Radtke (Molecules, 2021)
Li-rich and catalytically active <semantics>γ</semantics>-<semantics>LixV2O5</semantics> (x = 1.48) was investigated as a cathode for its heterogeneous charge transfer kinetics. Using a specially designed two-electrode system lithium half cell, Butler–Volmer analysis was performed, and Raman spectra were acquired in 18 mV intervals. A direct correlation was observed between the Raman shift of the active modes <semantics>Ag</semantics>,<semantics>Bg</semantics>, <semantics>Au</semantics>, and <semantics>Bu</semantics>, and the development of the Faraday current at the working electrode. The Raman intensity and the Raman shift were implemented to replace the current in a Tafel plot used for the analysis of Butler–Volmer kinetics. Striking similarities in the charge transfer proportionality constants <semantics>α</semantics> were found for current and Raman-based analysis. The potential of this new method of Raman-aided electrochemical detection at the diffraction limit is discussed.